Closure of the radial forearm free flap donor site with split-thickness skin graft or amniotic membrane: A prospective randomized clinical study. Issue 5 (May 2021) - Hunger, Stefan; Krennmair, Stefan; Stehrer, Raphael; Postl, Lukas; Brandner, Andreas; Malek, Michael
Abstract: The purpose of this study was to compare the clinical, aesthetic, and functional outcomes between amniotic membrane (test group) and split-thickness skin grafts (control group) used for radial forearm free flap defect closure. The primary outcome measurement for both groups was assessment of the defect closure healing process. In addition, aesthetic (Vancouver Scar Scale) and functional outcomes (skin sensitivity, hand/wrist functionality, grip strength) were evaluated. Fifty eligible patients with radial forearm free flap donor site defects were randomly assigned to two groups receiving either amniotic membrane (test group; n = 25) or split-thickness skin graft (control group; n = 25) for defect covering. Forty-seven of the 50 patients ( n = 47) were able to be followed up for 6 months and showed a significantly longer healing process ( p < 0.001) with amniotic membrane (64.5 ± 38.4 days; n = 24) than with split-thickness skin grafts (29.2 ± 8.9 days; n = 23); however, there were no differences in the prevalence of healing defects/dehiscence and/or wound infections. Forty-two of the 47 patients (21 in each group) were able to be continually followed up for 12 months, and showed no differences in terms of clinical outcome as well as the subjective and objective aesthetic and functional results evaluated. With regard to the clinical, aesthetic, and functional outcomes evaluated for radial forearm free flap defects, coverage with amniotic membrane offers an excellent alternative treatment approach, avoiding secondary induced donor site morbidity.